Respuesta :

Answer:

[tex] \boxed{\sf 15x^2 + 2} [/tex]

Step-by-step explanation:

Simplify the expression:

[tex] \sf \implies(10 {x}^{2} - 1 + 4x) + (3 + 5 {x}^{2} - 4x)[/tex]

Grouping like terms, 10x² + 5x² + 4 x - 4 x - 1 + 3 = (10 x² + 5x²) + (4 x - 4 x) + (-1 + 3):

[tex] \sf \implies (10 x^2 + 5 x^2) + (4 x - 4 x) + (-1 + 3)[/tex]

10x² + 5x² = 15x²:

[tex] \sf \implies 15 x^2 + (4 x - 4 x) + (-1 + 3)[/tex]

3 - 1 = 2:

[tex] \sf \implies 15 x^2 + (4 x - 4 x) + 2[/tex]

4 x - 4 x = 0:

[tex] \sf \implies 15 x^2 + 2[/tex]

ACCESS MORE